2017
DOI: 10.1186/s13256-017-1279-2
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated alveolar echinococcosis resembling metastatic malignancy: a case report

Abstract: BackgroundAlveolar echinococcosis is a potentially lethal zoonosis caused by larval forms of the tapeworm Echinococcus multilocularis.Humans are aberrant intermediate hosts who become infected by ingestion of egg-contaminated food or water or via physical contact with domestic or wild animals that carry the parasite in their small intestine. In humans, the disease usually affects the liver and can spread to other organs causing metastatic infiltration. In this report, we describe an advanced presentation of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Alveolar echinococcosis is often mistaken for a neoplastic growth, given its propensity for widespread organ infiltration with metastases (2). E. multilocularis may also imitate other diseases, including hepatic carcinoma, cirrhosis and tuberculosis, which may lead to improper diagnostic testing and delayed treatment (3,9,10). Diagnosis is confirmed based on a combination of clinical findings, epidemiological data, imaging, histopathology and/or nucleic acid detection and serology (8).…”
Section: How Humans Become Infectedmentioning
confidence: 99%
“…Alveolar echinococcosis is often mistaken for a neoplastic growth, given its propensity for widespread organ infiltration with metastases (2). E. multilocularis may also imitate other diseases, including hepatic carcinoma, cirrhosis and tuberculosis, which may lead to improper diagnostic testing and delayed treatment (3,9,10). Diagnosis is confirmed based on a combination of clinical findings, epidemiological data, imaging, histopathology and/or nucleic acid detection and serology (8).…”
Section: How Humans Become Infectedmentioning
confidence: 99%
“…Human AE is clinically/symptomatically often compared to liver cancer, since metacestodes exhibit progressive growth of lesions and a capacity to spread to other organs by metastatis formation [5, 72]. Nineteen out of the 28 dysregulated miRNAs identified in our study have been reported to be also affected in hepatocellular carcinoma (HCC) which is the most common type of primary liver cancer in adults [7381].…”
Section: Discussionmentioning
confidence: 99%
“…The ideal treatment for AE is still radical surgery, accompanied by chemotherapy. However, surgery is reserved for early-stage disease when lesions can be completely resected with a safe margin (≥ 2 cm) of unaffected tissue and no distant metastases [ 7 ]. Because most cases are found at an advanced stage, only 35% of patients can undergo curative surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%